ON THE QUINARY HOMOGENEOUS BI-QUADRATIC EQUATION x4  y4  x  yw3  14z2T 2 - M., A.Gopalan1; S., Aarthy Thangam2; O., .Ozer3 (university of eloued جامعة الوادي, 2020)
The purpose of this paper is to examine the non-zero distinct integral solutions of quinary biquadratic homogeneous diophantine equation x4  y4  x  yw3  14z2T 2 in integers. In this paper, we present some different patterns of integral solutions to the above diophantine equation in five variables. Also, we obtain some properties as relations between solutions and special numbers.
artical
Keywords: Quinary bi-quadratic equations, Diophantine equation, Special numbers, Integer solutions